Understanding tobacco industry tactics: a content analysis of newspaper coverage of tobacco issues in Pakistan - Sana Azmat Rana; Nadeem Iqbal (Tobacco Induced Diseases, 2018)
Background Each year more than 110,000 people die because of tobacco use in Pakistan. There are approximately 23.6 million (age 15-45 years) tobacco users in Pakistan. GYTS-2014 revealed that 13.3% of boys and 6.6% of girls (age 13-15 years) used tobacco products. Pakistan is the signatory of FCTC since 2004. Although efforts are being made but TI is continuously using its tactics targeting youth.The aim of this study is to examine the claims by tobacco industry as well as the counter-arguments by tobacco control advocates in the year 2016-17 in Pakistan to show patterns of arguments.